Dissecting the Generative AI Chatbot App Landscape: Distribution, Narratives, and Infrastructural Logics - Laezza, Vincenzo (Italian Sociological Review, 2026)
This study explores the distribution, organization, and narrative structures of applications integrating generative AI-based chatbots. Using a semantic network analysis combined with a qualitative walkthrough, it investigates how chatbot apps are thematically and functionally positioned within the digital ecosystem. Based on a corpus of 2,018 applications published between 2023 and 2024 and collected from major AI tool aggregators, the study identifies 16 modular clusters reflecting different functional and semantic logics. Results highlight the emergence of socio-technical hubs, the central role of foundational models like ChatGPT, and the progressive formation of infrastructural ecosystems that function as or are consolidating into super-app constellations. The research offers insights into how chatbot apps structure user interactions, operational practices, and socio-technical assemblages.